Differential social organization, collective action, and crime - Matsueda, Ross L. (Crime, law and social change, 2006)
This article elaborates and extends Sutherland’s [Principles of criminology (4th ed.), Lippincott, Philadelphia, Sutherland (1947)] concept of differential social organization, the sociological counterpart to his social psychological theory of differential association. Differential social organization contains a static structural component, which explains crime rates across groups, as well as a dynamic collective action component, which explains changes in crime rates over time. I argue that by drawing on George Herbert Mead’s [Mind, self, and society. University of Chicago Press, Chicago, Mead (1934)] theories of symbolic interaction and social control, we can conceptualize organization in favor of, and against, crime as collective behavior. We can then integrate theoretical mechanisms of models of collective behavior, including social network ties, collective action frames, and threshold models of collective action. I illustrate the integrated theory using examples of social movements against crime, neighborhood collective efficacy, and the code of the street.